Analisis Kelayakan Usahatani Jagung Di Desa Bantulanteh Kecamatan Tarano Kabupaten Sumbawa - sri juliarti juliarti; Suparmin Suparmin; efendy efendy (Department of Agricultural Social Economics Faculty of Agriculture University of Mataram, 2022)
The aims of this study were: (1) to analyze the costs and income of corn farming in Bantulanteh Village, Tarano District, Sumbawa Regency (2) to analyze what factors affect corn farming production in Bantulanteh Village, Tarano District, Sumbawa Regency (3) to analyze the feasibility corn farming in Bantulanteh Village, Tarano District, Sumbawa Regency. This study uses a descriptive method with the unit of analysis is Corn Farming in Bantulanteh Village, Tarano District, Sumbawa Regency. The location of the research was determined purposively, namely in all hamlets in Bantulanteh Village. Determination of the number of respondents using the Slovin method as many as 42 respondents, while sampling by simple random sampling. The types of data are quantitative and qualitative data, while the data sources are primary and secondary. The data collection technique is survey technique. The results showed that (1) the average production cost of corn farming in Bantulanteh Village was Rp. 15,576,844/LLG or Rp. 16,753,583/Ha, while the average income was Rp. 22,579,585/LLG or Rp. 24,285,341/Ha. (2) Simultaneously the production factors that significantly affect the production of corn farming are seeds, urea fertilizer, Phonska NPK fertilizer, labor and pesticides. Partially, the production factors that significantly influence the production of corn farming are seeds, while other production factors (urea fertilizer, Phonska NPK fertilizer, labor and pesticides) have no significant effect on corn farming production. (3) Corn farming in Bantulanteh Village is feasible to cultivate, this can be seen from the R/C Ratio value of 2.45 which is greater than 1, meaning that if Rp. 1 costs for maize farming, the farmer receives Rp. 2.45 income. Keywords: Corn Farming, Production Factors, Feasibility